2019
DOI: 10.1016/j.csbj.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Molecular Dynamics of Intrinsically Disordered Proteins and Their Fuzzy Complexes: A Mini-Review

Abstract: The molecular dynamics (MD) method is a promising approach toward elucidating the molecular mechanisms of intrinsically disordered regions (IDRs) of proteins and their fuzzy complexes . This mini-review introduces recent studies that apply MD simulations to investigate the molecular recognition of IDRs. Firstly, methodological issues by which MD simulations treat IDRs, such as developing force fields, treating periodic boundary conditions, and enhanced sampling approaches, are discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 106 publications
0
41
0
1
Order By: Relevance
“…We further performed MD simulations to gain insight into the binding features of p53 TAD1 and 1047. Given that force fields originally developed for ordered proteins are insufficient in sampling IDPs, 48,49 we firstly tested the newly developed force fields and water models parameterized for IDPs to better sample disordered p53 TAD1 ensemble. RSFF2 was developed by modifying the Amber ff99SB force field based on conformational free-energy distribution of the 20 amino acid residues from a protein coil library.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…We further performed MD simulations to gain insight into the binding features of p53 TAD1 and 1047. Given that force fields originally developed for ordered proteins are insufficient in sampling IDPs, 48,49 we firstly tested the newly developed force fields and water models parameterized for IDPs to better sample disordered p53 TAD1 ensemble. RSFF2 was developed by modifying the Amber ff99SB force field based on conformational free-energy distribution of the 20 amino acid residues from a protein coil library.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…Applications of the coarse-grained model to inves­tigate higher-order molecular assemblies are partially intro­ duced in Ref. [ 43 ], and their details are presented elsewhere.…”
Section: Examplementioning
confidence: 99%
“…Clustering of conformations was carried out based on the main‐chain conformation of p53TAD 2–60 in the last 300 ns of the simulations using a cutoff of 1.0 Å. The applied forcefield in combination with a four‐point water model (OPC waters – in this study) was shown to correctly reproduce the SAXS profiles of systems with extreme flexibility [54] …”
Section: Pdb Id Partner P53tad Region Methodsmentioning
confidence: 99%
“…The applied forcefield in combination with a four-point water model (OPC waters -in this study) was shown to correctly reproduce the SAXS profiles of systems with extreme flexibility. [54]…”
Section: Methodsmentioning
confidence: 99%